Dynamic regulation revisited: Signal dampening, experimentation and the ratchet effect - Thomas D. Jeitschko; John A. Withers (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
Regulators and the firms they regulate interact repeatedly. Over the course of these interactions, the regulator collects data that contains information about the firm's idiosyncratic private characteristics. This paper studies the case in which the regulator uses information gleaned from past cost observations when designing the current period's contract. Cost observations are obscured in stochastic settings and so perfect inferences about underlying private information are not possible. However, the design of the regulatory contract affects how much information is gleaned. When learning more about the firm's type, the regulator increases expected second period welfare by reducing distortions tied to asymmetric information. In contrast, by learning less about the firm's type, the regulator reduces incentive payments in first period. The trade-off between the desire to be more informed and to reduce incentive payments leads to a contracting dynamic that aligns with anecdotal, experimental and empirical evidence of the ratchet effect.
Keywords: D8; C73; L5; 330; Dynamic Contracts; Dynamic Agency; Ratchet Effect; Experimentation; Signal Dampening; Regulation